2019
DOI: 10.18632/aging.101963
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of gibberellin on human sperm motility

Abstract: Gibberellin, a plant growth regulator, is widely used to increase the shelf life and quality of fruits and vegetables. In this study, human semen samples were exposed to different concentrations of gibberellin, which reduced spermatozoa motility in vitro . Gibberellin exposure also increased levels of reactive oxygen species and the protein levels of apoptosis markers in human sperm. Gibberellin inhibited the activity of Na + /K + -adenosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Previous toxicological reports have suggested that GA 3 (oral, 150 μg/day) affected health in animals such as total protein levels, testosterone levels, and body weight. ,, Moreover, the oral agents of GA 3 (100 mg/mL of GA 3 ) could influence the sperm number and the quality of sperm chromatins, and then reduce the fertility in rats . Similar effect appeared in human sperm . Surprisingly, research shows decreased activity of Na + -K + -ATP enzyme and Ca 2+ -ATP enzyme and increased apoptosis rate of sperm cells when conducted by GA (2–4 mM). , This implies that gibberellin may inhibit human sperm motility as well.…”
Section: Effects Of Phytohormones On Animalsmentioning
confidence: 83%
“…Previous toxicological reports have suggested that GA 3 (oral, 150 μg/day) affected health in animals such as total protein levels, testosterone levels, and body weight. ,, Moreover, the oral agents of GA 3 (100 mg/mL of GA 3 ) could influence the sperm number and the quality of sperm chromatins, and then reduce the fertility in rats . Similar effect appeared in human sperm . Surprisingly, research shows decreased activity of Na + -K + -ATP enzyme and Ca 2+ -ATP enzyme and increased apoptosis rate of sperm cells when conducted by GA (2–4 mM). , This implies that gibberellin may inhibit human sperm motility as well.…”
Section: Effects Of Phytohormones On Animalsmentioning
confidence: 83%
“…Gibberellic acid [14][15][16][17][18], a complex tetracyclic diterpinoid, gives both auxin-like [14,15] and cytokinin-like [16] fits to nucleotide and cyclic nucleotide structures [17,18]. Templates 19-22 provide comparative fits of medicinal compounds that modulate cAMP levels via β 2adrenergic [19,20] and serotonin receptors [21,22]. RO363 and SC53116 are respectively β 2 -receptor and 5-HT 4 antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…21 In contrast, gibberellic acid may have an adverse effect on male physiology through reducing sperm motility. 22 Phytohormone classes differ in their ability to influence cGMP responses. Isner and coworkers established that cGMP levels are increased by abscisic acid, auxin and jasmonate in A. thaliana but not by cytokinins and brassinosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The ouabain sensitivity is maintained in the course of evolution and other growth factors or hormones such as Gibberellic acids (Gibberellins, GA) are used as plant growth regulators to stimulate both cell division and elongation that affect leaves and stems elongation as well as fruit ripening and flowering (76). Gibberellin in human cells increases the level of reactive oxygen species and protein apoptosis markers and GA inhibits the activity of the Na + /K + -ATPase and Ca 2+ -ATPase in human sperm (77).…”
Section: Genomic and Nongenomic Actions Of Thyroid Hormonesmentioning
confidence: 99%